Investigation on The Development of Three Person Basketball Match In Chengdu Colleges and Universities - Wang Guan; Wu Xuan (Ilmu Inovasi Nusantara, 2025)
Basketball is one of the most popular sports among college students, valued not only for its recreational and fitness benefits but also for its educational and social dimensions. In particular, three-player basketball, which is played on a half-court, represents a growing form of leisure sport that emphasizes participation, entertainment, and personal expression. Despite its increasing popularity in Chengdu, the development of three-player basketball in universities still encounters several problems, such as limited publicity, insufficient professional guidance, and uneven student participation. The purpose of this study is to investigate the current status, opportunities, and challenges of three-player basketball in colleges and universities in Chengdu, as well as to analyze students' perceptions and level of involvement. This study adopts a combination of research methods, including literature review, questionnaire survey, and mathematical statistics. Data were collected and analyzed to examine students' understanding of basketball, their interest in three-player basketball, and the organizational structure of related activities within campus settings. The findings of the study indicate that basketball is highly popular among Chengdu college students, with three-player basketball showing rapid development and promising market prospects. Male students tend to show greater enthusiasm and participation than female students, while most activities are organized by student associations rather than by the universities themselves. The main obstacles identified include insufficient awareness, a lack of systematic promotion, and the absence of professional coaching support. This study implies that universities should further promote and institutionalize three-player basketball as part of their sports programs. Strengthening publicity, providing professional guidance, and organizing more formal competitions will enhance students' physical fitness, enrich campus sports culture, and foster sustainable interest in basketball